Seronegative myasthenic crisis: a multicenter analysis - Mergenthaler, Philipp; Stetefeld, Henning R.; Dohmen, Christian; Kohler, Siegfried; Schoenenberger, Silvia; Boesel, Julian; Gerner, Stefan; Huttner, Hagen; Schneider, Hauke; Reichmann, Heinz; Fuhrer, Hannah; Berger, Benjamin; et al. (Journal of Neurology, 2022)
Myasthenic crisis (MC) is a life-threatening condition for patients with myasthenia gravis (MG). Seronegative patients represent around 10–15% of MG, but data on outcome of seronegative MCs are lacking. We performed a subgroup analysis of patients who presented with MC with either acetylcholine-receptor-antibody-positive MG (AChR-MG) or seronegative MG between 2006 and 2015 in a retrospective German multicenter study. We identified 15 seronegative MG patients with 17 MCs and 142 AChR-MG with 159 MCs. Seronegative MCs were younger (54.3 ± 14.5 vs 66.5 ± 16.3 years; p = 0.0037), had a higher rate of thymus hyperplasia (29.4% vs 3.1%; p = 0.0009), and were more likely to be female (58.8% vs 37.7%; p = 0.12) compared to AChR-MCs. Time between diagnosis of MG and MC was significantly longer in seronegative patients (8.2 ± 7.6 vs 3.1 ± 4.4 years; p < 0.0001). We found no differences in duration of mechanical ventilation (16.2 ± 15.8 vs 16.5 ± 15.9 days; p = 0.94) and length of stay at intensive care unit (17.6 ± 15.2 vs 17.8 ± 15.4 days; p = 0.96), or in-hospital mortality (11.8% vs. 10.1%; p = 0.69). We conclude that MC in seronegative MG affects younger patients after a longer period of disease, but that crisis treatment efficacy and outcome do not differ compared to AChR-MCs.
CRIS-Team Scopus Importer:2022-04-29
Keywords: Antibody status; Myasthenia gravis; Myasthenic crisis; Outcome; Seronegative